2004
DOI: 10.1165/rcmb.2003-0264oc
|View full text |Cite
|
Sign up to set email alerts
|

Rab3D and Actin Reveal Distinct Lamellar Body Subpopulations in Alveolar Epithelial Type II Cells

Abstract: Rab3D is a small GTP-binding protein associated with secretory vesicles in various exocrine and endocrine cells, where it has been implicated in regulated exocytosis. Data obtained previously in pancreas have suggested that rab3D is involved in the coating of secretory granules with filamentous actin. In the present study we employed Western blot analysis, immunofluorescence, and immunoelectron microscopy to examine the distribution of rab3D in rat lung. Rab3D immunoreactivity was detected in bronchiolar Clara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 32 publications
4
35
0
Order By: Relevance
“…Although we did not measure granule size in the present study, the increase in amylase levels we observed in AR42J cells overexpressing mycRab3Dwt may be a result of an increase in granule size and/or number. Others have demonstrated that Rab3D is associated with subpopulations of secretory granules [20,37] and is actually shed from granule membranes prior to exocytosis [19]. Valentijn et al [19] found that pancreatic granules engaging in exocytosis were coated with actin while Rab3D was released from the granule membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not measure granule size in the present study, the increase in amylase levels we observed in AR42J cells overexpressing mycRab3Dwt may be a result of an increase in granule size and/or number. Others have demonstrated that Rab3D is associated with subpopulations of secretory granules [20,37] and is actually shed from granule membranes prior to exocytosis [19]. Valentijn et al [19] found that pancreatic granules engaging in exocytosis were coated with actin while Rab3D was released from the granule membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is conceivable that secretion of surfactant is not merely a passive process, but requires additional mechanisms to be effective. Almost three decades ago, transmission electron micrographs of fused LBs suggested that actin is involved in expulsion (Tsilibary and Williams, 1983a;Tsilibary and Williams, 1983b) and immunostaining experiments confirmed that F-actin encloses individual LBs in proximity to the PM (van Weeren et al, 2004). We have recently shown that LBs are coated with actin following fusion with the PM (Miklavc et al, 2009b).…”
Section: Introductionmentioning
confidence: 92%
“…Loss of Rab27B function results in abnormal lung epithelium structure in mice, characterized by atrophy (Bolasco et al, 2011). Rab3D has been detected in type 2 alveolar pneumocytes, although its precise function remains unknown (van Weeren et al, 2004).…”
Section: Rab27b Expression and Localization 365mentioning
confidence: 99%